2009
DOI: 10.1074/jbc.m109.047381
|View full text |Cite
|
Sign up to set email alerts
|

Single Vesicle Millisecond Fusion Kinetics Reveals Number of SNARE Complexes Optimal for Fast SNARE-mediated Membrane Fusion

Abstract: SNAREs mediate membrane fusion in intracellular vesicle traffic and neuronal exocytosis. Reconstitution of membrane fusion in vitro proved that SNAREs constitute the minimal fusion machinery. However, the slow fusion rates observed in these systems are incompatible with those required in neurotransmission. Here we present a single vesicle fusion assay that records individual SNARE-mediated fusion events with millisecond time resolution. Docking and fusion of reconstituted synaptobrevin vesicles to target SNARE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
232
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 155 publications
(243 citation statements)
references
References 38 publications
(43 reference statements)
9
232
2
Order By: Relevance
“…To separate the docking and fusion steps of the overall fusion reaction, we reconstituted the different SNARE acceptor complexes into planar-supported bilayers. As expected from previous studies, the DN complex showed a much higher docking efficiency than the syntaxin:SNAP-25(CHAPS) complex (4,5), while the syntaxin:SNAP-25(DPC) complex purified in DPC docked synaptobrevin-2 vesicles docked almost as efficiently as the DN complex (Fig. 1 b; Fig.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…To separate the docking and fusion steps of the overall fusion reaction, we reconstituted the different SNARE acceptor complexes into planar-supported bilayers. As expected from previous studies, the DN complex showed a much higher docking efficiency than the syntaxin:SNAP-25(CHAPS) complex (4,5), while the syntaxin:SNAP-25(DPC) complex purified in DPC docked synaptobrevin-2 vesicles docked almost as efficiently as the DN complex (Fig. 1 b; Fig.…”
Section: Resultssupporting
confidence: 88%
“…1 d). As described in Domanska et al (5), the initial fast component of the fusion kinetics was examined and fit with a parallel-activation mixed fusion-site model. Similar numbers of activation steps (~7 5 1) were found for each complex, and the fast rates of fusion ranged between 60 and 150 s À1 for all investigated complexes (5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies have left open the possibility that the number of SNARE complexes that cooperate during fusion is variable (11,12), much attention has been given to the notion of a preferred number of SNARE complexes, with estimates varying from a single SNARE complex (13) to 15 (14), although more recent estimates vary between two and eight (12,(15)(16)(17)(18). Unfortunately, this large disparity in results has not been appropriately explained, and it remains unclear whether the differences are a result of inherent properties of the particular set of SNAREs involved or rather originate from the biophysical characteristics of the fusing vesicles.…”
Section: Exocytosis | Fusion Intermediate | Liposome Dockingmentioning
confidence: 99%